Parallel connected inverter for fuel cell system - Younis, M.A.A.; Rahim, N.A.; Mekhilef, Saad (2008)
This paper presents the design and analysis of a new configuration of parallel connected inverter suitable for fuel cell system application. The configuration consists of dc/dc converter and parallel three-phase dc/ac inverter. Series resistors added to the inverter output to maintain same current in each inverter of the two parallel inverters, and to reduce the circulating current in the parallel inverters to minimum. Third harmonic injection PWM (THIPWM) reduces the total harmonic distortion and to make maximum use of the voltage source. DSP was used to create the THIPWM and the control algorithm for the converter. PID controller is applied on the full-bridge dc/dc converter side to maintain the ac voltage to the required level. Experimental results have been shown to validate the proposed system.